2023
DOI: 10.3390/jcm13010050
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Composition and Physical Activity Level in Students of Medical Faculties

Aleksandra Jaremków,
Iwona Markiewicz-Górka,
Wojciech Hajdusianek
et al.

Abstract: Maintaining an active lifestyle is crucial for good health. Markers of health risk include tissue components. This study aimed to indicate which body composition elements create the strongest correlations with physical activity performed in young students of medical faculties. The study group consisted of 75 students (33 men and 42 women) from Wroclaw Medical University. Each student underwent accelerometer and anthropometric measurements and body composition analysis. Both men and women had similar physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Higher BMI in the group with higher levels of physical activity resulted from a higher body cell mass (p < 0.01) but not from a percentage difference in body fat (p > 0.4) [31]. A related study found that the amount of vigorous physical activity correlated significantly with the basal metabolic rate (BMR), fat, water, and muscle content, fat-free mass (FFM), bone mass, extracellular to intracellular water ratio (ECW/ICW), and phase angle (PA) [39]. Similar results were obtained in our own studies, with a statistically significant correlation between a higher level of PhA and higher levels of physical activity among students.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher BMI in the group with higher levels of physical activity resulted from a higher body cell mass (p < 0.01) but not from a percentage difference in body fat (p > 0.4) [31]. A related study found that the amount of vigorous physical activity correlated significantly with the basal metabolic rate (BMR), fat, water, and muscle content, fat-free mass (FFM), bone mass, extracellular to intracellular water ratio (ECW/ICW), and phase angle (PA) [39]. Similar results were obtained in our own studies, with a statistically significant correlation between a higher level of PhA and higher levels of physical activity among students.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the World Obesity Federation estimates that by 2035, onethird of adult Poles (33%) will be obese [37]. In a study conducted among medical students in Wrocław, normal body weight was observed in 80% of the students [39]. The situation among students in Krosno looks somewhat better, but already 22.7% of the respondents are overweight, and 8.7% are obese.…”
Section: Discussionmentioning
confidence: 99%